2020
DOI: 10.1002/jcph.1580
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Similarity in Antipsychotic Exposure‐Response Relationships in Clinical Trials Between Adults and Adolescents With Acute Exacerbation of Schizophrenia

Abstract: Despite agreement that early‐onset schizophrenia is continuous with the adult‐onset form, quantitative relationships between antipsychotic exposure and clinical response are relatively unexplored in adolescents, compared to adults. Clinical efficacy data from second‐generation antipsychotic development programs (N = 5951 adults and N = 1035 adolescents ranging from 12 to 17 years old) were collected from available new drug applications submitted to the US Food and Drug Administration from 1993 to 2017. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Both databases included positive, negative (studies that demonstrate no difference in effect on the primary end point between treatment and placebo arms), and failed trials (studies that demonstrated no difference in effect on the primary end point between active control and placebo arms). Trial, demographic, and clinical characteristics for each patient population enrolled have been described previously 14–17 …”
Section: Confirming Extrapolation Of Efficacy For Bipolar I Disorder and Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Both databases included positive, negative (studies that demonstrate no difference in effect on the primary end point between treatment and placebo arms), and failed trials (studies that demonstrated no difference in effect on the primary end point between active control and placebo arms). Trial, demographic, and clinical characteristics for each patient population enrolled have been described previously 14–17 …”
Section: Confirming Extrapolation Of Efficacy For Bipolar I Disorder and Schizophreniamentioning
confidence: 99%
“…Protocols across different drugs and between adult and pediatric patients differed with regard to the number of samples collected and the sampling times. To derive exposures at steady state at each clinical assessment, adult and pediatric pharmacokinetic models were used to simulate various exposure metrics (ie, average concentration, trough concentration, maximum concentration, and area under the curve) 15 . Figures 2 and 3 provide visual comparisons of the exposure‐response relationship in patients with schizophrenia and bipolar I disorder, respectively.…”
Section: Confirming Extrapolation Of Efficacy For Bipolar I Disorder and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to accelerate and optimize pediatric drug development, regulatory agencies may allow efficacy to be extrapolated from adults to pediatrics according to the evidence‐based assumptions that disease characteristics and response to therapy are similar in adult and pediatric populations 7‐9 . In schizophrenia, these assumptions have been demonstrated using clinical efficacy data from atypical antipsychotic development programs 2,10,11 . Consequently, in 2020, the US Food and Drug Administration (FDA) released a general advice letter to sponsors permitting the efficacy of atypical antipsychotics for the treatment of schizophrenia in adults to be extrapolated to pediatric patients aged 13 years or older, provided that the drug has the respective approved indication in adults, and shares a similar mechanism of action to current FDA‐approved antipsychotics (dopamine D 2 receptor antagonism or partial agonism, serotonin 5‐HT 1A receptor partial agonism, and/or serotonin 5‐HT 2A receptor antagonism) 2 .…”
mentioning
confidence: 99%
“…[7][8][9] In schizophrenia, these assumptions have been demonstrated using clinical efficacy data from atypical antipsychotic devel-opment programs. 2,10,11 Consequently, in 2020, the US Food and Drug Administration (FDA) released a general advice letter to sponsors permitting the efficacy of atypical antipsychotics for the treatment of schizophrenia in adults to be extrapolated to pediatric patients aged 13 years or older, provided that the drug has the respective approved indication in adults, and shares a similar mechanism of action to current FDA-approved antipsychotics (dopamine D 2 receptor antagonism or partial agonism, serotonin 5-HT 1A receptor partial agonism, and/or serotonin 5-HT 2A receptor antagonism). 2 In addition, a pharmacokinetic (PK) analysis to justify dose selection and a safety study in adolescent patients are required.…”
mentioning
confidence: 99%